2017
DOI: 10.26623/jdsb.v18i1.555
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Current Ratio, Inventory Turn Over Dan Debt to Equity Ratio Pada Perusahaan Otomotif Dan Produk Komponennya Pada Bursa Efek Indonesia ( 2010 – 2013)

Abstract: <p>Penelitian ini dilakukan untuk menguji pengaruh variabel <em>Current Ratio, Inventory Turnover, Debt to Equity Ratio (DER</em>), terhadap <em>Return on Asset</em> (ROA) pada perusahaan automotive and allied products yang terdaftar di Bursa Efek Indonesia (BEI) periode 2010-2013. Sampel penelitian sebanyak 17 perusahaan otomotif dan produk komponen.</p><p>                Hasil dari penelitian menggunakan analisis regresi berganda, yang menunjukkan bahwa <em>cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Hasil penelitian menurut Mahardika dan Marbun (2016) serta Wedyaningsih dkk (2019), mengatakan bahwa variabel debt to equity ratio berpengaruh negatif terhadap profitabilitas. Berbeda dengan penelitian yang dilakukan oleh Kridasusila dan Rachmawati (2016), bahwa variabel debt to equity ratio berpengaruh positif terhadap profitabilitas. Menurut Efendi dan Wibowo (2017) ,debt to asset ratio berpengaruh positif dan signifikan terhadap profitabilitas.…”
Section: Pendahuluanunclassified
“…Hasil penelitian menurut Mahardika dan Marbun (2016) serta Wedyaningsih dkk (2019), mengatakan bahwa variabel debt to equity ratio berpengaruh negatif terhadap profitabilitas. Berbeda dengan penelitian yang dilakukan oleh Kridasusila dan Rachmawati (2016), bahwa variabel debt to equity ratio berpengaruh positif terhadap profitabilitas. Menurut Efendi dan Wibowo (2017) ,debt to asset ratio berpengaruh positif dan signifikan terhadap profitabilitas.…”
Section: Pendahuluanunclassified
“…Consistently, Setiawan (2015) also showed a positive and significant relationship between Inventory Turnover and ROA of food and beverage companies listed on IDX from 2010 to 2013. Kridasusila & Rachmawati (2016) also resulted in the same relationship between both variables. However, the research done by Irman & Iswara (2019) concluded that Inventory Turnover does not have a significant effect on ROA.…”
Section: Profitabilitymentioning
confidence: 57%
“…However, the research done by Hendawati (2017) shows that total assets turnover does not have any influence on ROE. Kridasusila & Rachmawati (2016) and Setiawan (2015) showed significant influence on Return on Assets, while Widiyanti & Bakar (2014) concluded a positive and significant relationship between Inventory Turnover and profitability. In contrary, Sari & Budiasih (2014) found in their study that Inventory Turnover does not have any influence on profitability.…”
Section: Introductionmentioning
confidence: 94%
“…The effect in question is that any increase in the Current Ratio will always be followed by an increase in Return On Assets (ROA) and vice versa. And if the Current Ratio has decreased, it will be followed by a decrease in Return On Assets (ROA) (Kridasusila & Rachmawati, 2017).…”
Section: Effect Of Current Ratio On Profitability (Roa)mentioning
confidence: 99%